A fluorescent photochromic diarylethene based on naphthalic anhydride with strong solvatochromism. Issue 47 (8th June 2017) - Chen, Shangjun; Li, Xin; Song, Liwen
Abstract : A diarylethene molecule consisting of an 1, 8-naphthalic anhydride and two 2, 5 dimethylthiophene which exhibits reversible fluorescence switching capacity as well as solvatochromism with red shift of the fluorescence maximum by more than 150 nm. Abstract : A novel "push–pull" diarylethene molecule consisting of an electron withdrawing ethene bridge (1, 8-naphthalic anhydride) and two moderate electron donating side chains (2, 5-dimethylthiophene) has been designed and synthesized. The photochromism study, together with density functional theory calculations, revealed that the molecule exhibits reversible fluorescence switching capacity upon photo-isomerization and remarkable solvatochromism with red shift of the fluorescence maximum by more than 150 nm owing to intramolecular charge transfer.